(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Organic farming is a holistic production management system. A study was conducted on the case of organic farming in andhrapradesh (India). Majority of the respondent farmers were satisfied with contract organic farming. Technical guidance and inputs were provided by firms. Most of the farm operations were done by respondents manually. Machines should be made available to the firms.In today‟s world organic food products was very important for the human beings to lead a healthy life. have become a basic necessity in human life. In this paper, an attempt has been made to find out the consumers awareness towards organic food. A sample of 400 respondents‟ was purposively selected from Tirupur District. The selected samples are analyzed using simple percentage, chi-square test and multiple regression analysis test. It is found that three variables namely there exists any significant association between gender, age, educational qualification, monthly income and consumer awareness towards organic food products of the respondents.